A NEW METHOD FOR THE SIZE AND PERFORMANCE ANALYSES AND OPTIMIZATION OF THERMAL SYSTEMS: THE EXERGY DENSITY - Karakurt, Asim Sinan; Sahin, Bahri (YILDIZ TECHNICAL UNIV, 2019)
With the acceptance of thermodynamics as a science field, an important step has been taken in the transition from thermal systems produced by trial and error method to planned and calculated systems which are produced according to determined standards. During this time, many performance criteria have been proposed and some of them have been widely used in design phases and in practical applications. In this study, the interaction between the performance and size of the thermal systems is examined by using a new proposed criterion, the exergy density, as a thermodynamic state property. The effects of pressure and temperature of working fluid on the exergy density values are obtained and property graphics are plotted. In addition to these, case studies for the air standard cycles (Otto, Diesel, Atkinson and Brayton) and a steam power (Rankine) cycle have been carried out. As a result, the proposed criterion or property for thermal systems has been shown to be beneficial in the design phase as it examines system dimensions as well as system performance.
Keywords: Exergy; exergy density; thermal systems; exergetic size; Engineering